Load frequency control of microgrids - Khokhar, Bhuvnesh; Parmar, K P Singh; Thakur, Tripta; Kothari, D. P. (CRC Press : Taylor & Francis Group, 2024)
The book focuses on describing the emerging microgrid concept, and its various constituents, especially the EV technology, and investigates the load frequency control performance of different microgrid configurations by implementing the modern control theory. An exhaustive study is presented on the various renewable energy sources and an up-to-date status of their installed capacity and power generation. The text presents case studies for load frequency control of a microgrid in its various operating modes